KOHENSI GRAMATIKAL DAN LEKSIKAL DALAM CERPEN ”MADU LOMUQ” KARYA KORRIE LAYUN RAMPAN - Nurul Masfufah (Kantor Bahasa Kalimantan Timur, 2016)
This paper is about discourse in a short story “Madu Lomuq” by Korrie Layun Rampan. It studies the short story’s lexical and grammatical cohesion. The data are sentences in “Madu Lomuq”. It uses distributional method. It applies direct elemental analysis as the basic techniques followed by substitution, deletion, and covering mark reading techniques as advanced techniques. The result shows that there are (1) grammatical cohesion markers, such as references, comparisons, substitutions, ellipses, conjunctions, inversions, and passivizations and also (2) lexical cohesion markers, such as repetitions, synonyms, antonyms, text’s overall cohesion, and collocations.